The impact of artificial intelligence on digital integration prospects in the Eurasian Economic Union and the Union State - Bochkov, Dmitry A. (Journal of the Belarusian State University. International Relations, 2026)
This article examines the geopolitical risks and security risks arising from the rapid deployment of artificial intelligence in the absence of binding international legal standards. As states increasingly apply artificial intelligence in military contexts, it has acquired clear dual-use characteristics, which may intensify geopolitical competition and security dilemmas. For the member states of the Eurasian Economic Union, this trend constitutes a significant contemporary challenge. Because international legal regulation remains fragmented, states are independently developing national regulatory frameworks for artificial intelligence systems. Divergent national approaches, uneven technological development among states, and the acceleration of artificial intelligence related arms competition compound these difficulties. The article analyses the economic, humanitarian, and military risks associated with artificial intelligence and proposes strategies to address these regulatory gaps, contextualised within the national interests of the Republic of Belarus and its partners in regional integration alliances. The author concludes that deeper digital integration and the establishment of a «belt of digital good-neighbourliness» may contribute to sustainable development and the protection of national sovereignty in the contemporary technological landscape.